Army diplomacy : American military occupation and foreign policy after World War II - Hudson, Walter M. (Judge advocate) (Battles and campaigns (Lexington, Ky.), 2015)
'Army Diplomacy' demonstrates how, in the immediate aftermath of World War II, the United States Army became the principal agent of American foreign policy. The army designed, implemented, and administered the occupations of the defeated Axis powers Germany and Japan, as well as many other nations.